Unraveling the risk factors for spontaneous intra cerebral hemorrhage among West Africans (2020)
"Abstract Objective To characterize risk factors for spontaneous intra cerebral hemorrhage (sICH) occurrence and severity among West Africans. Methods The Stroke Investigative Research and Educational Network (SIREN) study is a multicenter case control study involving 15 sites in Ghana and Nigeria. Patients were adults ≥18 years old with CT confirmed sICH with age-, sex-, and ethnicity-matched stroke-free community controls. Standard instruments were used to assess vascular, lifestyle, and psychosocial factors. Factors associated with sICH and its severity were assessed using conditional logistic regression to estimate odds ratios (ORs) and population-attributable risks (PARs) with 95% confidence intervals (CIs) for factors. Results Of 2,944 adjudicated stroke cases, 854 were intra cerebral hemorrhage (ICH). Mean age of patients with ICH was 54.7 ± 13.9 years, with a male preponderance (63.1%), and 77.3% were non lobar. Etiologic subtypes of sICH included hypertension (80.9%), structural vascular anomalies (4.0%), cerebral amyloid angiopathy (0.7%), systemic illnesses (0.5%), medication-related (0.4%), and undetermined (13.7%). Eight factors independently associated with sICH occurrence by decreasing order of PAR with their adjusted OR (95% CI) were hypertension, 66.63 (20.78–213.72); dyslipidemia, 2.95 (1.84–4.74); meat consumption, 1.55 (1.01–2.38); family history of CVD, 2.22 (1.41–3.50); non consumption of green vegetables, 3.61 (2.07–6.31); diabetes mellitus, 2.11 (1.29–3.46); stress, 1.68 (1.03–2.77); and current tobacco use, 14.27 (2.09–97.47). Factors associated with severe sICH using an NIH Stroke Scale score >15 with adjusted OR (95% CI) were non consumption of leafy green vegetables, 2.03 (1.43–2.88); systolic blood pressure for each mm Hg rise, 1.01 (1.00–1.01); presence of midline shift, 1.54 (1.11–2.13); lobar ICH, 1.72 (1.16–2.55); and supratentorial bleeds, 2.17 (1.06–4.46). Conclusions Population-level control of the dominant factors will substantially mitigate the burden of sICH in West Africa.